2022
DOI: 10.3389/fchem.2022.1069816
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of tetracycline hydrochloride with g-C3N4/Ag/AgBr composites

Abstract: Graphite carbon nitride (g-C3N4), as a polymer semiconductor photocatalyst, is widely used in the treatment of photocatalytic environmental pollution. In this work, a Z-scheme g-C3N4/Ag/AgBr heterojunction photocatalyst was prepared based on the preparation of a g-C3N4-based heterojunction via in-situ loading through photoreduction method. The g-C3N4/Ag/AgBr composite showed an excellent photocatalytic performance in the degradation of tetracycline hydrochloride pollutants. Among the prepared samples, g-C3N4/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…20,33 The binding energies of Br 3d 5/2 and Br 3d 3/2 were 67.5 and 68.5 eV, indicating that the negative valence of Br existed in the system. 21,23,25,31,32…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,33 The binding energies of Br 3d 5/2 and Br 3d 3/2 were 67.5 and 68.5 eV, indicating that the negative valence of Br existed in the system. 21,23,25,31,32…”
Section: Resultsmentioning
confidence: 99%
“…Ag was used as an electron storage pool, and a ternary heterojunction was constructed, which enhanced the separation of the photogenerated electron-hole pairs and improved the photocatalytic degradation of TMA. 25 Using ESR to study the effective photogenerated carriers produced by photoexcited samples more intuitively. Fig.…”
Section: Photoelectric Property Analysismentioning
confidence: 99%
“…Wang et al first reported the characteristics of CN for hydrogen production from water [ 10 ]. Since then, it has set off a research boom in the field of photocatalysis [ 11 , 12 , 13 , 14 , 15 ]. In the research of photocatalytic hydrogen production, the conduction band (−1.4 eV) and valence band (1.3 eV) potentials of CN meet the thermodynamic conditions (3.0 > Eg > 1.23 eV) for water splitting to generate H 2 and O 2 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used for photocatalytic H 2 and O 2 production, selective photocatalytic organic synthesis, and degradation of organic and/or inorganic pollutants photocatalytically under visible light. [10][11][12][13][14][15] On the other hand, due to its polymeric nature, some problems still persist in using g-C 3 N 4 as a photocatalyst, such as small specific surface area, crucial photoinduced electron-hole recombination, low quantum yield, and extensive bandgap, which slow down the adequate utilization of sunlight. 16 Despite this, studies have shown that C 3 N 4 's photogenerated electrons are localized within tri-s-triazinebased building blocks, causing a high recombination rate of electron-hole pairs and preventing photocatalysis.…”
Section: Introductionmentioning
confidence: 99%